Life Design Counseling outcome and process: A case study with an adolescent - Cardoso, Paulo (2016)
This article aims to explore the relationship between clients' narrative transformation and the promotion of vocational decidedness and career maturity in a mid-adolescent case of Life Design Counseling (LDC). To assess LDC outcomes the Vocational Certainty Scale and the Career Maturity Inventory — Form C were used before and after the intervention. To intensively analyze the process of LDC change two measures of narrative change were used: the Innovative Moments Coding System (IMCS), as a measure of innovation emergence, and the Return to the Problem Coding System (RPCS), as a measure of ambivalence towards change. The results show that the three LDC sessions produced a significant change in vocational certainty but not in career maturity. Findings confirm that the process of change, according to the IMCS, is similar to the one observed in previous studies with adults. Implications for future research and practice are discussed.